453 Novel combination immunotherapy for boosting and priming immune responses in pancreatic cancer: strong anti-tumour effects with interleukin-15 and CD40 agonist treatment. (9th November 2020) - Audenaerde, Jonas Van; Marcq, Elly; Scheidt, Bianca von; Davey, Ashleigh; Oliver, Amanda; Waele, Jorrit De; Quatannens, Delphine; Loenhout, Jinthe Van; Pauwels, Patrick; Roeyen, Geert; Lardon, Filip; Slaney, Clare; et al.
Abstract : Background: With the poorest 5-year survival of all cancers, improving treatment for pancreatic cancer is one of the biggest challenges in cancer research. In this era of combination immunotherapies, we sought to explore the potential of combining both priming and activation of the immune system. To achieve this, we combined a CD40 agonist with interleukin-15 and tested its potential in pancreatic cancer. Methods: Two different mouse models of pancreatic cancer were used to assess the potential of this combination regimen. Therefore, effects on tumour growth kinetics and survival were charted. Differential effects on immune signatures was investigated using RNA sequencing. Functional immune subset involvement was tested using different immune depletion experiments and multicolour flow cytometry in different relevant immune sites. Immune memory was checked using re-challenge experiments. Results: We demonstrated profound reduction in tumour growth and increased survival of mice with the majority of mice being cured when both agents were combined, including an unprecedented dose reduction of CD40 agonist without losing any efficacy (fig 1). RNA sequencing analysis showed involvement of natural killer cell and T cell mediated anti-tumour responses and the importance of antigen-presenting cell pathways. This combination resulted in enhanced infiltration of tumours by both cytotoxic T cells and natural killer cells, as well as a striking increase in the ratio of CD8+ T cells over T regulatory cells. We also observed a significant increase in numbers of dendritic cells in tumour draining lymph nodes, particularly CD103+ dendritic cells with cross-presentation potential. A critical role for CD8+ T cells and involvement of natural killer cells in the anti-tumour effect was highlighted. Importantly, strong immune memory was established, with an increase in memory CD8+ T cells only when both interleukin-15 and the CD40 agonist were combined. Conclusions: We demonstrated profound synergistic anti-tumour effects upon combination of CD40 agonist and interleukin-15 treatment in mouse models of pancreatic cancer. This preclinical data supports initiation of a first-in-human clinical trial with this combination immunotherapy strategy in pancreatic cancer.